Coherently driven microcavity-polaritons and the question of superfluidity - R. T. Juggins; J. Keeling; M. H. Szymańska (Nature Communications, 2018)
Driven-dissipative microcavity polariton experiments find superfluid-like behaviour but the intuition developed from equilibrium systems cannot be straightforwardly applied. Juggins et al. show coherently-driven polaritons are not superfluid and earlier observations instead arise from a distinct rigid state.